Quality of Family Planning Services Affects Acceptor Satisfaction During the Covid-19 Pandemic - Mufdlilah; Riska Dwi Pramita Sari; Hakimi, Mohammad (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The rapid spread of the Covid-19 virus has impacted economic, social, environmental, and health challenges. One of them is maternal and child health services, such as reducing contraceptive use by 10% in some low and middle-income countries (LMIC) to prevent and control COVID-19. Quality family planning services affect satisfaction and correlate with continuity of family planning use. This study aims to determine the relationship between family planning acceptor satisfaction and the quality of family planning services during the COVID-19 pandemic. This study used quantitative research with a cross-sectional. The study population was women of child-bearing age (WCBA) aged 15-49 years who received non-natural family planning services in Sleman Regency, Yogyakarta, starting in March 2020. The sampling technique used was consecutive sampling. All research data were collected online (Google Forms). The total sample size was 171 respondents. The analysis used was the Chi-Square test and logistic regression. The results showed that the satisfaction of family planning acceptors with the quality of family planning services during the COVID-19 pandemic in Sleman Regency was 93.6%. There is a significant relationship between the satisfaction of family planning acceptors and the quality of family planning services in tangible, reliability, responsiveness, assurance, and empathy (p < 0.05). There was no association between family planning acceptor satisfaction with age, occupation, education, and health facilities. The quality of family planning services with the tangible dimension was 8.376 times more likely to result in family planning acceptor satisfaction (p=0.026; 95% CI=1.284-54.631). Strengthening cooperation between health service providers, health workers, and all relevant stakeholders is needed to maintain the quality of family planning services, and ensuring the availability and access to family planning services in the community is a strategy for family planning services in the new normal of the coming era.